A geochemical investigation of the Lake Sibiya system, Northern Zululand - Whyte, Stewart Rodney (Department of Geological Sciences, 2016)
Lake Sibaya (27°15'-21'25'S; 32°32'-32°44'E) is situated in the northern region of the Zululand coastal plain, and is remarkable in that it embodies a near-pristine· freshwater coastal lake preserving clear residual signs of its former estuarine origin. Despite the· fact that the lake constitutes perhaps the most intensively studied of all freshwater bodies in South Africa, little is known .of its geochemical character. The objective of this study was therefore to conduct an investigation of the waters and sediments of the lake system, which might then provide a chemical baseline against which the future environmental quality of the system could be gauged, and in terms of which the current functioning of the ecosystem can be better understood. In line with this rationale, water and sediment samples were collected from each of fourteen sampling sites located along three transects running, variously, S-N, SW-NE and W-E across peripheral arms of the lake. Waters in direct contact with the sediments were thoroughly agitated with the sediments and thereafter decanted for analysis. Since the lake is purported to be fed almost exclusively by groundwater flow, water samples were collected from three groundwater . . wells located north-west of the lake. The Department of Water Affairs (DW AF) databases for groundwater chemistry, and for lake level and chemistry over the period 1980 to 1998, were used to supplement this data, and to provide an indication of any medium-term parameter changes. A water sample was also· collected from the non-perennial Mseleni River, although the river is known to contribute minimally to the lake volume. The majority of laboratory analyses were conducted within the Department of Geological Sciences at the University of Cape Town, adhering to standard analytical methods wherever possible.